Saccharomyces cerevisiae: a novel and efficient biological control agent for Colletotrichum acutatum during pre-harvest - Lopes, Marcos Roberto; Klein, Mariana Nadjara [UNESP]; Ferraz, Luriany Pornpeo [UNESP]; Silva, Aline Caroline da; Kupper, Katia Cristina [UNESP] (Elsevier B.V., 2015)
In this study, we evaluated the efficiency of six isolates of Saccharomyces cerevisiae in controlling Colletotrichum acutatum, the causal agent of postbloom fruit drop that occur in pre-harvest citrus. We analyzed the mechanisms of action involved in biological control such as: production of antifungal compounds, nutrient competition, detection of killer activity, and production of hydrolytic enzymes of the isolates of S. cerevisiae on C. acutatum and their efficiency in controlling postbloom fruit drop on detached citrus flowers. Our results showed that all six S. cerevisiae isolates produced antifungal compounds, competed for nutrients, inhibited pathogen germination, and produced killer activity and hydrolytic enzymes when in contact with the fungus wall. The isolates were able to control the disease when detached flowers were artificially inoculated, both preventively and curatively. In this work we identified a novel potential biological control agent for C acutatum during pre-harvest. This is the first report of yeast efficiency for the biocontrol of postbloom fruit drop, which represents an important contribution to the field of biocontrol of diseases affecting citrus populations worldwide. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Detached citrus flowers; Antifungal compounds; Killer yeast; Hydrolytic enzymes; Postbloom fruit drop